Further evaluation of general and descriptive praise statements on the acquisition of tacts. (4th August 2022) - Cortes, Adrian; Wiskow, Katie M.
Abstract: Praise is a consequence that many practitioners use in teaching settings and descriptive praise is often recommended. However, research on descriptive praise has not reliably resulted in faster acquisition compared to general praise. Delivering short praise statements may increase the effectiveness of descriptive praise by only presenting the relevant feature of the feedback (i.e., the target). In the present study, we evaluated general, descriptive, and general plus descriptive praise statements on acquisition of tacts via telehealth with two typically developing toddlers. Results showed that the number of sessions to criterion was similar in all conditions for both participants, which suggests that the contents of praise did not influence learning. This study also builds on the research of praise through the preliminary use of telehealth with toddlers.